The effects of positional role on tactical behaviour in a four-a-side small-sided and conditioning soccer game (Kinesiology, 2019)
In soccer different tactical functions are necessary to perform individual well, as a team. The demands of players from different positional roles can be manipulated on training through small-sided and conditioned games and tactical behaviours might be stimulated. The aim of this study is to assess the effects of positional role in tactical behaviour of U-17 youth soccer players based on core tactical principles in a four-a-side small-sided and conditioned game. The sample comprised of 268 U-17 youth Brazilian soccer players. They were divided into five positional roles: centre backs; fullbacks; defensive midfielders; offensive midfielders; and forwards. The instrument used to collect and analyse data was the System of Tactical Assessment in Soccer (FUT-SAT). Results revealed that players from different positional roles showed no differences in the quantity of tactical actions performed. Moreover, forwards showed lower quality of tactical behaviour in both the defensive phase and in actions far from the ball that ensures team cohesion in the defensive phase compared to fullbacks. This study showed that the four-a-side format allows U-17 players to perform a similar quantity of tactical actions regardless of their positional role, but the player’s positional role influence their quality of tactical behaviour. Therefore, this structure might be used for trainings that promotes similar tasks and stimuli for players’ development that do not focus on specific tactical roles.